Jawabanmu

2014-05-30T21:07:31+07:00
X^4 + px^3 - 12x^2 + (q+28)x -15 mempunyai faktor x²-2x+1
x²-2x+1 = (x-1)(x-1)
(x-1)=0 ----> x=1
rumus Horner

   1                  1            p            -12              q+28                -15
                                     1             p+1            p-11                p+q+17
                       1          p+1          p-11           p+q+17            p+q+2

p+q+2=0
p+q = -2
ya kan x^4 +px^3 +qx - (12x^2 +28x - 15) diubah jadi x^4 + px^3 - 12x^2 +qx + 28x - 15 .
jadi x^4 + px^3 - 12x^2 + (q+28)x -15
tadi ada revisi sedikit
jadi p+q+2=0 maka p+q = -2
Mkch yea kak :-)